The Influence of The Psychology of Family Relations on The Development of a Child's Personality (Open Academia: Journal of Scholarly Research, 2023)
The article discusses the main directions of socialization of personality in the family, the influence of interpersonal relationships in the family on the social development of the child. On the basis of a differentiated approach, the features of maternal and paternal upbringing in the family and their impact on the social development of the individual are revealed.